2012
DOI: 10.4236/as.2012.34059
|View full text |Cite
|
Sign up to set email alerts
|

Control of volunteer adzuki bean in soybean

Abstract: ABSTRACT, and imazethapyr applied PRE provided up to 6%, 24%, 14%, 8%, and 0% control, respectively at 8 weeks after emergence (WAE), while acifluorfen, fomesafen, bentazon, thifensulfuron-methyl, cloransulam-methyl, imazethapyr, and imazethapyr plus bentazon applied POST provided 2%, 2%, 5%, 34%, 6%, 4%, and 12% control, respectively at 8 weeks after application (WAA). Generally, with the aforementioned herbicides, soybean yield was equivalent to the weedy control and soybean grain contamination with adzuki b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…angularis) was domesticated in China ∼12,000 y ago (1) and is grown in more than 30 countries of the world, especially in East Asia (2,3). Adzuki bean seed is an important source of protein, starch, mineral elements, and vitamins (4,5).…”
mentioning
confidence: 99%
“…angularis) was domesticated in China ∼12,000 y ago (1) and is grown in more than 30 countries of the world, especially in East Asia (2,3). Adzuki bean seed is an important source of protein, starch, mineral elements, and vitamins (4,5).…”
mentioning
confidence: 99%
“…Seeds should be planted 2.5-3.8 cm deep, in rows spaced 60-90 cm apart (Hardman et al 1989;Hang et al 1993;HDC 2014). Each pod contains 4-12 wine-red seeds that measure 5-7.5 mm long and 4-5.5 mm wide; slightly smaller than a soybean seed (Duke 2012;Kramer et al 2012). In part, due to slow initial seed imbibition, adzuki bean seedlings emerge 10-20 d after sowing (Hardman et al 1989;Yoshida et al 1995).…”
Section: Adzuki Bean Biologymentioning
confidence: 99%
“…The weedy persistence of transiently grown domesticated adzuki bean cultivars in Japan suggests an incomplete removal of seed dormancy, despite breeding efforts (Kaga et al 2008). Likewise, Ontario producers have observed volunteer adzuki bean up to 10 yr following production (Kramer et al 2012). While not tested in soil, Lumpkin and McClary (1994) reported that adzuki bean seed stored at 15% relative humidity and 14% seed moisture content retained 96% germination for 10 yr.…”
Section: Adzuki Bean Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…The adzuki bean (Vigna angularis), which contains starch, nutritious proteins, and vitamins and has a sweet taste, has been used as an ingredient in traditional dessert foods, particularly in East Asian countries such as Korea, China, and Japan [1][2][3]. Adzuki beans have been extensively cultivated in more than 30 countries worldwide [4][5][6]. Additionally, international food trade has dramatically increased owing to the development of food storage and transportation technologies.…”
Section: Introductionmentioning
confidence: 99%